Dual Mechanisms of Action of Self-Delivering, Anti-HIV-1 FANA Oligonucleotides as a Potential New Approach to HIV Therapy - Mayumi Takahashi; Haitang Li; Jiehua Zhou; Pritsana Chomchan; Veenu Aishwarya; Masad J. Damha; John J. Rossi (Elsevier, 2019)
Currently, the most effective and durable therapeutic option for HIV-1 infection is combination antiretroviral therapy (cART). Although cART is powerful and can delay viral evolution of drug resistance for decades, it is associated with limitations, including an inability to eradicate the virus and a potential for adverse effects. Therefore, it is imperative to discover new HIV therapeutic modalities. In this study, we designed, characterized, and evaluated the in vitro potency of 2'-deoxy-2'-fluoroarabinonucleotide (FANA) modified antisense oligonucleotides (ASOs) targeting highly conserved regions in the HIV-1 genome. Carrier-free cellular internalization of FANA ASOs resulted in strong suppression of HIV-1 replication in HIV-1-infected human primary cells. In vitro mechanistic studies suggested that the inhibitory effect of FANA ASOs can be attributed to RNase H1 activation and steric hindrance of dimerization. Using 5'-RACE PCR and sequencing analysis, we confirmed the presence of human RNase H1-mediated target RNA cleavage products in cells treated with FANA ASOs. We observed no overt cytotoxicity or immune responses upon FANA ASO treatment. Together, our results strongly suggest that FANA ASOs hold great promise for antiretroviral therapy. The dual ability of FANA ASOs to target RNA by recruiting RNase H1 and/or sterically blocking RNA dimerization further enhances their therapeutic potential. Keywords: HIV-1, antisense oligonucleotide, ASO, 2'-deoxy-2'-fluoro-D-arabinonucleic acid, FANA, gymnosis, RNase H1, gapmer, steric blocker